2016
DOI: 10.1016/j.forsciint.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A thermoanalytical, X-ray diffraction and petrographic approach to the forensic assessment of fire affected concrete in the United Arab Emirates

Abstract: A thermoanalytical, X-ray diffraction and petrographic approach to the forensic assessment of fire affected concrete in the United Arab Emirates Alqassim, M. A.; Jones, Martyn; Berlouis, L. E. A.; Nic Daeid, Niamh General rightsCopyright and moral rights for the publications made accessible in Discovery Research Portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.•… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The diffraction peak intensity of Ca(OH) 2 (2θ = 18.08° and 34.12°) had no obvious change with the increasing temperature from 20°C to 400°C. However, this peak intensity was eliminated after 600°C nearly, similar to what was observed by Alqassim et al (2016) and Delhomme et al (2012). On the other hand, it was worth noting that the diffraction peak intensity of CaO (2θ = 37.42°) appeared after 600°C and it increased with the increasing temperature.…”
Section: Mineralogical Analysessupporting
confidence: 82%
See 3 more Smart Citations
“…The diffraction peak intensity of Ca(OH) 2 (2θ = 18.08° and 34.12°) had no obvious change with the increasing temperature from 20°C to 400°C. However, this peak intensity was eliminated after 600°C nearly, similar to what was observed by Alqassim et al (2016) and Delhomme et al (2012). On the other hand, it was worth noting that the diffraction peak intensity of CaO (2θ = 37.42°) appeared after 600°C and it increased with the increasing temperature.…”
Section: Mineralogical Analysessupporting
confidence: 82%
“…A similar tendency for NSC with 0% and 20% BFS was also observed by Siddique and Kaur (2012). Different from reports of Alqassim et al (2016) and Siddique and Kaur (2012), Poon et al (2001) found that the residual compressive strength increase occurred when HSC with 30% and 40% BFS was subjected to 200°C, yet after 600°C, the residual compressive strength drastically reduced by about 40% -50% compared to that at room temperature. According to the above discussion and the result reported by Sanjayan and Stocks (1993), HSC containing BFS will appear to be inferior elevated temperature resistance as compared to NSC containing BFS.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…show that there was a considerable reduction of both flexural strength and residual flexural strength in the temperature range of 500 and 800 °C, which can be mainly explained by the chemical changes of concrete in this temperature region [25][26][27]. Possible reasons can be reactions in the cement stone such as dehydration of Ca(OH)2 below 500 °C, and decomposition of CSH (calcium-silicate-hydrates) and CaCO3 between 500 and 800 °C.…”
Section: Flexural Behavior With Different Type Of Fiber and Temperatumentioning
confidence: 94%